Determination of Real-Time Polymerase Chain Reaction Uncertainty of Measurement Using Replicate Analysis and a Graphical User Interface with Fieller’s Theorem - James Ian Stuart; Johan Delport; Robert Lannigan; George Zahariadis (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Disease monitoring of viruses using real-time polymerase chain reaction (PCR) requires knowledge of the precision of the test to determine what constitutes a significant change. Calculation of quantitative PCR confidence limits requires bivariate statistical methods.